3D Self-Supported NiS2/Ti3C2Tx-CC Composite Electrode for High-Performance Flexible Supercapacitors. Issue 1 (13th June 2022) - He, Liping; Wu, Fang; Fang, Liang; Hu, Jia; Luo, Haijun; Zhang, Shufang; Hu, Baoshan; Zhou, Miao
Abstract: In this paper, a flexible self-supported electrode based on the porous composite of NiS2 and Ti3 C2 Tx grown on carbon cloth (NiS2 /Ti3 C2 Tx -CC) was designed and synthesized. Due to the introduction of highly conductive and flexible Ti3 C2 Tx, the NiS2 /Ti3 C2 Tx -CC electrode achieves a 1.4-fold increase (1214 C g -1 at 2 A g -1 ) in the specific capacity, a 1.3-fold increase in the rate capability (63% of capacity retention with the current density increases from 2 to 20 A g -1 ), and a 2.0-fold increase in the cyclic stability (∼83% of capacity retention at the current density of 20 A g -1 after 2000 charge–discharge cycles) compared with the NiS2 -CC electrode. Meanwhile, there is no obvious capacity attenuation at the bending angle of 180°, indicating the prominent flexibility of the NiS2 /Ti3 C2 Tx -CC electrode. Accordingly, an all-solid asymmetric supercapacitor (ASC) is fabricated, which exhibits a high energy density of 57.55 Wh kg -1 at the power density of 800 W kg -1 . Furthermore, ∼97% of initial capacity is maintained at the current density of 5 A g -1 after 1000 charge–discharge cycles, indicating the good cycling stability. These satisfactory electrochemical behaviors can be also ascribed to the introduction of Ti3 C2 Tx, which can facilitate the rapid electron transport at the interface of the composite and maintain the outstanding mechanical integrality of the electrode during charge–discharge processes.